Incipient Motion of Sediment in Open Channel : A Comparison between Laboratory Data and Site Observation - Bong, Charles Hin Joo; Tze, Liang Lau; Aminuddin, Bin Ab Ghani (2012)
This paper aims at evaluating whether the design criteria based on critical velocity or critical shear stress is more suitable for the purpose of self-cleansing in open concrete drain. Experimental work on incipient motion was done in rectangular flume with two different widths namely 0.3 m and 0.6 m. The results from the incipient motion experiment were compared with a short-term on-site observation on the erosion and deposition pattern in a stretch of urban open concrete drain located in a residential area in Kuching, Sarawak, Malaysia. Comparison with site observation has shown that the relationship between mean critical velocity with median grain size; c = dV 50 + 246.0075.0 developed from the experimental work predicts reasonably well when erosion starts to occur on site. The critical shear stress values obtained from the experimental work tend to under predict when compare with the values from site observation. Thus, the mean critical velocity is a much better criterion to be used in the design for open concrete drain for self-cleansing purpose.